2020
DOI: 10.1186/s12974-020-01811-7
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic microglia influence developing hypothalamic glial populations

Abstract: Background: Although historically microglia were thought to be immature in the fetal brain, evidence of purposeful interactions between these immune cells and nearby neural progenitors is becoming established. Here, we examined the influence of embryonic microglia on gliogenesis within the developing tuberal hypothalamus, a region later important for energy balance, reproduction, and thermoregulation. Methods: We used immunohistochemistry to quantify the location and numbers of glial cells in the embryonic bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 91 publications
1
27
2
Order By: Relevance
“…Accumulating evidence indicates that WM and developing microglia, contribute to myelinogenesis/oligodendrocyte progenitor maintenance 6466 ; thus, we next explored the effects of filling the brain with repopulating cells on WM and WM-associated cells. However, unlike during development in which these cells participate in oligo/myelinogenesis, in 28d recovery mice we observe no changes in Olig2, a marker for cells of oligodendrocyte lineage (Figure S5A, D), PDGFRα, a marker for oligodendrocyte progenitor cells (Figure S5B, E), or MBP, a marker for myelin (Figure S5C, F-G).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that WM and developing microglia, contribute to myelinogenesis/oligodendrocyte progenitor maintenance 6466 ; thus, we next explored the effects of filling the brain with repopulating cells on WM and WM-associated cells. However, unlike during development in which these cells participate in oligo/myelinogenesis, in 28d recovery mice we observe no changes in Olig2, a marker for cells of oligodendrocyte lineage (Figure S5A, D), PDGFRα, a marker for oligodendrocyte progenitor cells (Figure S5B, E), or MBP, a marker for myelin (Figure S5C, F-G).…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies, again using DT-mediated ablation of NG2-expressing cells, have provided the first indications of a role of OPCs in the maintenance of brain immune homeostasis and, while it has been known for some time that microglia can regulate the behavior and differentiation of OPCs (reviewed by Domingues et al, 2016 ), these studies have shown that OPCs can, in turn, modulate microglia (Zhang S.-Z. et al, 2019 ; Liu and Aguzzi, 2020 ; Marsters et al, 2020 ; Mecha et al, 2020 ). In the absence of NG2-positive OPCs, microglia become hypersensitive to lipopolysaccharide (LPS) injection, resulting in microglial activation and neuroinflammation (Zhang S.-Z.…”
Section: Genetic Technologiesmentioning
confidence: 99%
“…CD11c + microglia, which expand in the postnatal brain, express a neurosupportive gene signature and IGF-1 and are required for myelinogenesis during development ( 75 ). More recently, a new role in gliogenesis has been identified for microglia at the later embryonic stages of E15.5 and E17.5 ( 76 ). A subpopulation of amoeboid microglia lining the tuberal hypothalamic third ventricle have been found to influence glial precursors via chemokine signaling, namely, CCL2 and CXCL10, which are required for the migration and maturation of oligodendrocytes, but not astrocytes ( 76 ).…”
Section: A Day In the Life Of Microglia: Functions In The Embryonic Amentioning
confidence: 99%
“…More recently, a new role in gliogenesis has been identified for microglia at the later embryonic stages of E15.5 and E17.5 ( 76 ). A subpopulation of amoeboid microglia lining the tuberal hypothalamic third ventricle have been found to influence glial precursors via chemokine signaling, namely, CCL2 and CXCL10, which are required for the migration and maturation of oligodendrocytes, but not astrocytes ( 76 ). An additional unique microglial subset ( i.e .…”
Section: A Day In the Life Of Microglia: Functions In The Embryonic Amentioning
confidence: 99%
See 1 more Smart Citation